Personal and Moral Identity
VI, 327 p.
Keywords: The subject of personal and moral identity is at the centre of interest, not only of academic research within disciplines such as philosophy and psychology, but also of everyday thinking. This is why the Neth erlands School for Research in Practical Philosophy and the Institute for Ethics of the Vrije Universiteit in Amsterdam took the initiative to bring together scholars from various disciplines, interested in the subject. The expert-seminar on 'Personal and Moral Identity' took place from 12-14 January 1999. Financial contributions from the Vrije Universiteit, the Dutch Scientific Organisation (NWO) and the Royal Dutch Academy for the Sciences (KNA W) made the event possible. The chapters in this book either go back to papers presented at the seminar or were written afterwards by participants, inspired by the discussions that took place during the seminar. We are very grateful to Dr. Hendrik Hutter for his assistance in editing the texts and making the manuscript camera-ready. December 2001, The Editors. 1 Introduction Albert W. Musschenga Although scholars studying the identity of persons usually address diverging issues and have different research agendas, there is a grow ing awareness that one may benefit from insights and results present in other disciplines dealing with that subject. This explains the enthu siastic responses to the invitation of the Netherlands School for Research in Practical Philosophy and the Institute for Ethics of the Vrije Universiteit to participate in a seminar on 'Personal and Moral Identity'.